1994
DOI: 10.1007/bf00348196
|View full text |Cite
|
Sign up to set email alerts
|

Management of locally advanced breast cancer

Abstract: The management of locally advanced breast cancer with single modality therapy has been associated with a high rate of systemic failure. A multimodality treatment strategy that includes induction cytotoxic chemotherapy, surgery, radiation therapy, and, possibly, hormonal ablation therapy is the current preferred management approach. As our knowledge and understanding of the mechanisms involved in mitogenic signal transduction improve, it is likely that less toxic, more efficacious agents will emerge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…With the recognition that the results of surgical therapy were disappointing, radiotherapy was utilized for palliation. In the 1980s several authors reported the results of systematic study of multimodality therapy of LABC [13, 14, 15, 16, 17, 18, 19, 20, 21], and multimodality therapy has since become the norm for the management for LABC [22].…”
Section: Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…With the recognition that the results of surgical therapy were disappointing, radiotherapy was utilized for palliation. In the 1980s several authors reported the results of systematic study of multimodality therapy of LABC [13, 14, 15, 16, 17, 18, 19, 20, 21], and multimodality therapy has since become the norm for the management for LABC [22].…”
Section: Historical Perspectivementioning
confidence: 99%
“…Surgery in combination with radiotherapy offers superior local control rates [20, 24, 31, 40, 41, 42, 43, 44, 45, 46, 47, 48]. Improvement in local control rates can be achieved with higher radiation dosages at the expense of higher complication rates [22]. Surgical resection is an important tool in the attainment of local control, even in extensively pretreated patients [39].…”
Section: Local Therapy: Surgery and Radiotherapymentioning
confidence: 99%
“…Many authors have found an improvement in local control rates and-in some series-survival if surgery is included in the man- agement [19 -21, 25, 35-42]. Reviewers recommend its inclusion in the treatment of locally advanced breast cancer [19,[43][44][45]. The use of the LDMF for wound cover allows for wide resection of big, otherwise unresectable lesions [46].…”
Section: Discussionmentioning
confidence: 99%